Effect of Tech-Facilitated Gender-Based Violence on social media communication in Nigeria - Funmi Falobi (Budapest International Research and Critics University, 2025)
Tech-Facilitated Gender-Based Violence (TFGBV) has become a significant issue in the global context, including in Nigeria, where the rapid growth of social media use intersects with existing gender-based inequalities. In Nigeria, the effects of TFGBV on social media communication are both profound and wide-ranging, influencing individuals, communities, and even the broader societal discourse. Misogyny and tech-facilitated gender-based violence (TFGBV) are escalating concerns in Nigeria, reflecting broader societal gender inequalities exacerbated by digital technologies. This paper explores the evolving trends, contexts, and impacts of TFGBV, including online harassment, cyberstalking, doxxing, and non-consensual sharing of intimate images. Social media and digital platforms have become both sites of empowerment and oppression, where misogynistic narratives thrive, often with limited legal and institutional accountability. Cultural norms, weak regulatory frameworks, and inadequate enforcement mechanisms further enable perpetrators while silencing victims. Through a critical analysis of case studies, policy responses, and advocacy efforts, this study highlights the urgent need for comprehensive legal reforms, digital literacy programs, and multi-stakeholder collaborations to combat TFGBV. Addressing these issues is essential for fostering a safer digital environment and advancing gender equality in Nigeria.